Are there no wage returns to compulsory schooling in Germany? A reassessment - Cygan-Rehm, Kamila (Journal of Applied Econometrics, 2021)
This study replicates and challenges the finding of zero wage returns to compulsory schooling in Germany by Pischke and von Wachter (Review of Economics and Statistics, 90(3), 592–598), which is unusual in the literature yet widely cited and until now uncontradicted. I document that this finding is sensitive to minor changes in sample restrictions and model specification. Further results suggest that their estimates are potentially confounded by previously unconsidered institutional details. These findings render the conclusion that compulsory schooling in Germany yields no wage returns at a minimum controversial.
CRIS-Team Scopus Importer:2021-09-10

Bounding the causal effect of unemployment on mental health - nonparametric evidence from four countries - Cygan-Rehm, Kamila; Kühnle, Daniel; Oberfichtner, Michael (Health Economics, 2017)

Do working hours affect health? Evidence from statutory workweek regulations in Germany - Cygan-Rehm, Kamila; Wunder, Christoph (Labour Economics, 2018)

Employment effects of payroll tax subsidies - Collischon, Matthias; Cygan-Rehm, Kamila; Riphahn, Regina Therese (Small Business Economics, 2021)
This paper exploits several reforms of wage subsidies in the framework of the German Minijob program to investigate substitution and complementarity relationships between subsidized and non-subsidized labor demand. We apply an instrumental variables approach and use administrative data on German establishments for the period 1999–2014. Particularly in small establishments (0–9 employees), subsidized Minijob employment comprises large shares of the work force, on average over 40%. For these establishments, robust evidence shows that increasing the subsidization of Minijob employment crowds out non-subsidized employment. Our results imply that Minijob employment in 2014 may have eliminated more than 0.5 million unsubsidized employment relationships just in small establishments. This represents an unintended and harmful consequence of the Minijob subsidy.
CRIS-Team Scopus Importer:2020-10-23
Keywords: C26; Crowding out effect; Displacement effect; Employment; J21; J23; J38; L26; Labor demand; Minijob; Payroll tax; Substitution effect; Wage subsidy

Immigrant Fertility in Germany: The Role of Culture - Cygan-Rehm, Kamila (Schmollers Jahrbuch, 2014)

Paid parental leave and families' living arrangements - Riphahn, Regina Therese; Cygan-Rehm, Kamila; Kühnle, Daniel (Labour Economics, 2018)
Keywords: Gender

Teenage Pregnancies and Births in Germany: Patterns and Developments - Riphahn, Regina Therese; Cygan-Rehm, Kamila (Applied economics, 2014)

The effect of education on fertility: Evidence from a compulsory schooling reform - Cygan-Rehm, Kamila; Mäder, Miriam Gesa (Labour Economics, 2013)
This paper investigates the effect of education on fertility under inflexible labor market conditions. We exploit exogenous variation from a German compulsory schooling reform to deal with the endogeneity of education. By using data from two complementary datasets, we examine different fertility outcomes over the life cycle. In contrast to evidence for other developed countries, we find that increased education causally reduces completed fertility. This negative effect operates through a postponement of first births away from teenage years and no catch-up later in life. We attribute these findings to the particularly high opportunity costs of childrearing in Germany. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Fertility; Education; Childlessness; Timing of births; Educational reform